(untitled) (Fractal: Journal of Psychology, 2009)
From a research on academic productions related to housing issues, aiming to map subjectivities constructed in shelters, we analyzed texts (books, articles, theses and dissertations) about the issue from the period between 2000 and 2008. We studied the material carefully in order to give visibility to the discourses and practices that are being produced, outlining a brief history of assistance and protection measures to children and youth in Brazil. From the content of the texts were raised different categories of analysis, but here we have decided to focus on the discussions about one of them: "Network of Shelter Assistance". Taking the reference of the Speech Analysis, this article analyses the protection networks from the public policies which guarantee the rights of children and adolescents. We noticed that most studied texts mentioned the fragility of these networks as responsible for the protection and retention of children and adolescents in shelters.